EFFECT OF DIFFERENT PLANT EXTRACTS AS ANTIFUNGAL AGENTS AGAINST ALTERNARIA ALTERNATA CAUSING LEAF BLIGHT DISEASE OF CABBAGE (BRASSICA OLERACEA) - ANSAR. A,; NARESH. L,; SIMON. S., (International Journal of Pharma and Bio Sciences, 2015)
Plants historically have served as models in drug development. The production of medicines and the pharmacological treatment of diseases began with the use of herbs. The antifungal activity of five different plants namely, Aegle marmelos, Carica papaya, Mentha arvensis, Nicotiana plumbaginifolia and Tamarindus indica were tested against plant pathogenic fungi Alternaria alternata. The plant extracts were prepared in three solvents like acetone, methanol, and n-hexane. All the plants tested exhibited varying degrees of antifungal activity; however, the methanolic extract of Aegle marmelos showed maximum antifungal activity with the minimum growth zone of 7 mm at 24 hrs and 12 mm at 72 hrs as compared to control.